Modelo de control para la gestión administrativa de las pymes agrícolas en el Cantón Valencia, Provincia de los Ríos 2015. - Quintana Reyes, Alexandra Carolina (2016)
This research project was conducted in the canton Valencia province of Los Rios, he had as designing a control model for the administrative management of agricultural SMEs, for this has been carried out the analysis of the different aspects involved in this purpose investigation. After evaluating the current situation of SMEs and have a clear overview of the activities taking place in is, we proceeded to make a proposal in order that farmers can carry out good governance. So that for the contextual framework of the investigation were taken into account issues such as; introduction, general objective and specific objectives. However, in the framework topics and subtopics that have to do with the investigation in relation to definitions and concepts as detailed; business, management, control, types, characteristics, principles, hierarchical levels, so definitions of SMEs is, importances, characteristics, strengths and weaknesses, advantages and disadvantages of them. As a descriptive and inductive and applied research for the development of analytical research project methods were used, all with the support of primary and secondary sources that allowed data collection. To obtain the results surveys were executed to 53 SMEs, obtaining the information needed to meet the proposed objectives, data were tabulated in the Excel application. The interpretation of the results were not entirely satisfactory, so the 69.81% do not have staff to perform the role of control in your company, and 81.13% do not have control standards so that they are not having an excellent management. Conclusions and recommendations, which were obtained after making the analysis of research were formalized. Bibliographical sources underlying concepts and definitions. The interview form, and photos of the executed survey is attached. Keywords: SMEs, administrative management, control.